2021
DOI: 10.3390/geomatics1030020
|View full text |Cite
|
Sign up to set email alerts
|

The Results of Applying Different Methodologies to 10 Years of Quantitative Precipitation Estimation in Catalonia Using Weather Radar

Abstract: The single polarization C-Band weather radar network of the Meteorological Service of Catalonia covers the entire region (32,000 km2), which allows it to apply a series of corrections that improve preliminary estimations of the rainfall field (hourly and daily). In addition, an automatic re-processing using automatic weather stations helps to incorporate ground-based information. The last process of the quantitative precipitation estimation (QPE) is running the end-product again eight days later, when the data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Weather radars have become very beneficial for identifying, tracking and nowcasting thunderstorms and their associated meteors (severe weather or heavy rainfall). The main advantages are spatial and temporal resolutions on the order of 1 km 2 and 5 min, respectively [4,5]. These scales are compatible with those associated with the resolution of severe weather phenomena [6].…”
Section: Introductionsupporting
confidence: 54%
“…Weather radars have become very beneficial for identifying, tracking and nowcasting thunderstorms and their associated meteors (severe weather or heavy rainfall). The main advantages are spatial and temporal resolutions on the order of 1 km 2 and 5 min, respectively [4,5]. These scales are compatible with those associated with the resolution of severe weather phenomena [6].…”
Section: Introductionsupporting
confidence: 54%
“…The analysis considered the maximum daily VIL fields to simplify the procedure instead of the 6 min maps. More details about the capabilities and limitations of the radar network are discussed in [27].…”
Section: Weather Radarmentioning
confidence: 99%
“…All the products are planar except the 3D CAPPI (Constant Altitude Plan Position Indicator) product, which consists of 40 planar fields with a height step of 0.5 km (from 0.5 to 20 km). Apart from the CAPPI, the other products are Echo Top of 12 dBZ reflectivity (TOP12) [32], and the 24 h Quantitative Precipitation Estimation (QPE) using radar and rain gauges of automatic weather stations [7,33]. Green points in the left panel of Figure 1 show the location of the different singlepol C-band radars of the Catalan network.…”
mentioning
confidence: 99%
“…The region of interest is well-covered by the composition products, with scarce affectation caused by beam blockage. It is important to note that the QPE product is composed of radar and automatic weather station data, using geo-statistical techniques as it was introduced in [33]. That research showed that by combining both sources the QPE fields were very reliable because the new field introduces the quantitative information provided by rain gauges and the qualitative distribution of precipitation observed by radar.…”
mentioning
confidence: 99%